Materials for Civil Engineering : Properties and Applications in Infrastructure - Lee, Luke S.; Estrada, Hector (McGraw-Hill's AccessEngineering., 2020)
"This comprehensive textbook offers detailed coverage of the properties of the construction materials that civil engineers use in the field. Students will learn about material characteristics and find out how to analyze material properties and select appropriate materials for civil engineering projects of all types and sizes. Materials for Civil Engineering : Properties and Applications in Infrastructure begins with an introduction to basic materials science and selection, and contains subsequent chapters devoted to steel, concrete, masonry, wood, asphalt, aggregates, and FRP composites. Key characteristics, manufacturing processes, and sustainability issues associated with each type of material are included. Data analysis of materials is emphasized throughout, with references to ASTM standards for material testing".